Development of Audiovisual Media for Reproductive Health Education for Parents of Adolescents - Kusumaningrum, Tanjung Anitasari Indah; Inayati, Nurul Latifatul; Asyanti, Setia; Umaroh, Ayu Khoirotul; Livia, Wardhatul; Laili, Ramadani Nur; Trijaya, Trijaya; Dewanti, Ririn Cahya; Kusumawati, Yuli; Arifah, Izzatul (UI Scholars Hub, 2025)
Parents are the primary source of information for adolescents, but many parents lack an understanding of health materials. For knowledge to be increased, health media, one of which is audiovisual media, are desirable. This study aimed to develop audiovisual media on adolescents’ reproductive health. Media development utilized the analyze, design, develop, implement, and evaluate (ADDIE) model. The respondents in this study were parents of adolescents aged 10–14 years, comprising 10 parents in the small group evaluation, 20 in the field evaluation, and 10 in the implementation stage. The effectiveness of the media was tested through pretests and posttests. Using a questionnaire tested for validity and reliability, the data were collected. The effectiveness of the media was analyzed using N-gain. The results revealed that the seven audiovisual media were suitable for use. At the implementation stage, the N-gain value was 0.55, indicating that the video effectively increased parents’ knowledge of reproductive health. Developing audiovisual media on reproductive health is effective for parents. To ensure parents truly grasp reproductive health information, health institutions should consider creating interactive audiovisual resources. This format would make the material more accessible and comprehensible.